IL-25 and IL-33 induce Type 2 inflammation in basophils from subjects with allergic asthma. Issue 1 (December 2016) - Salter, Brittany; Oliveria, John; Nusca, Graeme; Smith, Steve; Tworek, Damian; Mitchell, Patrick; Watson, Rick; Sehmi, Roma; Gauvreau, Gail
Abstract Background The alarmin cytokines IL-25 and IL-33 are key promoters of type 2 inflammation. Basophils respond to alarmin cytokines, however the relationship of these cytokines with basophil activation and recruitment in human studies of allergic asthma has not been well characterized. This study investigated the effect of IL-25 and IL-33 on basophils in a model of allergic asthma. Methods 10 mild allergic asthmatics underwent allergen and diluent inhalation challenges. Bone marrow aspirates were collected at pre-challenge and 24 h (h) post challenge. Peripheral blood and sputum samples were collected at pre-challenge, 7 h, and 24 h post-challenge to measure basophil expression of IL-17RB, ST2, and intracellular IL-25. Freshly isolated peripheral blood basophils from allergic donors were incubated overnight with IL-25 and IL-33, or sputum supernatant collected post-allergen to assess pro-inflammatory effects of mediators released in the airways. Results There were increased percentage of basophils expressing IL-17RB, ST2, and intracellular IL-25 collected from bone marrow, peripheral blood, and sputum after allergen inhalation challenge. In vitro stimulation with IL-25 and IL-33 increased the percentage of basophils expressing intracellular type 2 cytokines and surface activation markers, and primed eotaxin-induced migratory potential of basophils, which was mediated directly through IL-17RB and ST2, respectively. Stimulation of basophils with sputum supernatants collected post-allergen challenge up-regulated the percentage of basophils expressing markers of activation and intracellular type 2 cytokines, which was reversed following blockade of the common β chain (βc). Conclusions Our findings indicate that the alarmin cytokines IL-33 and IL-25 increase basophil activation and migratory potential, and may pose as a novel therapeutic targets for the treatment of allergic asthma.